2002
DOI: 10.1006/viro.2002.1502
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Steady-State Levels of “High Risk” but Not “Low Risk” Human Papillomavirus (HPV) E6 Proteins Are Increased by Inhibition of Proteasome-Dependent Degradation Independent of Their p53- and E6AP-Binding Capabilities

Abstract: The group of mucosal epithelia-infecting human papillomaviruses (HPV) can be subdivided in "low" and "high risk" HPV types. Both types induce benign neoplasia (condyloma), but only the infection with a "high risk" HPV type is causally associated with an increased risk of developing anogenital tumors. The oncogenic potential of high risk HPVs resides at least partially in the viral E6 protein. The E6 protein targets the cellular p53 protein for proteasome-dependent degradation, which is associated with the immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 62 publications
5
32
0
4
Order By: Relevance
“…Conversely, if the silencing of E6AP led to a concomitant decrease in E6 protein levels, we would have expected our microarray results to be similar to those observed, and while our overall conclusionthat all E6 functions are dependent on E6AP-would have been the same, the underlying mechanism would have been quite distinct. Importantly, however, there are no reports in the literature to suggest that E6AP affects E6 protein expression levels, and a previous study has shown that steady-state levels of functional, epitope-tagged E6 proteins are not influenced, either positively or negatively, by their ability to interact with E6AP (28). It therefore seems unlikely that the silencing of E6AP would have affected E6 protein levels in our experiments.…”
Section: Vol 79 2005 Effects Of E6 and E6ap On Gene Expression Profmentioning
confidence: 66%
“…Conversely, if the silencing of E6AP led to a concomitant decrease in E6 protein levels, we would have expected our microarray results to be similar to those observed, and while our overall conclusionthat all E6 functions are dependent on E6AP-would have been the same, the underlying mechanism would have been quite distinct. Importantly, however, there are no reports in the literature to suggest that E6AP affects E6 protein expression levels, and a previous study has shown that steady-state levels of functional, epitope-tagged E6 proteins are not influenced, either positively or negatively, by their ability to interact with E6AP (28). It therefore seems unlikely that the silencing of E6AP would have affected E6 protein levels in our experiments.…”
Section: Vol 79 2005 Effects Of E6 and E6ap On Gene Expression Profmentioning
confidence: 66%
“…Interestingly, the levels are restored by proteasome inhibitor treatment 2 hr before harvesting. Both E6 and E6*I are stabilized by MG132 suggesting that not only full-length E6 23 but also E6*I is degraded along the proteasome pathway. As a control we also carried out the same fractionation experiment on the wt HPV-18 E6 construct and on a HPV-16 E7 expressing construct, to show that the localization is consistent with that of the 2 proteins taken singularly (Fig.…”
Section: Hpv-18 E6*i Regulates the Levels Of Hpv-18 Full-length E6mentioning
confidence: 99%
“…It has also been suggested that the subcellular localiza-tion of E6 is essential for its p53 degradation activity, based on the observation that high-risk HPV16, -18, and -31 E6 proteins can localize to the nucleus after transfection whereas low-risk HPV6 and -11 E6 proteins are predominantly cytoplasmic (35,37,41,57,59,60,63), although HPV11 E6 has also been detected in the nucleus (24). In another study, the expression levels of E6 have been shown to vary between high-and low-risk types (31). Specifically, high-risk HPV16 E6 was shown to possess a lower steadystate expression level than E6 from the low-risk HPV6 and -11 or the cutaneous HPV5 and -8.…”
mentioning
confidence: 99%